Study on tower crane / Nurul Hayati Abdul Halim, Mastura Yaakob and Ainun Mansor - Abdul Halim, Nurul Hayati; Yaakob, Mastura; Mansor, Ainun (Faculty of Mechanical Engineering, 2003)
A nation that moves towards development, industrialization cannot avoid using machines as part of the devices of operations. In the construction industry, tower crane is widely used as an important devise for the operations. The purpose of this project is to study the concepts of tower crane in terms of their functions requirement, performances, purpose of design, economics and many more. We also considered safety measures and improvement in the quality of the machine’s operations.